Management of phaco complications newer techniques - Agarwal, Amar; Narang, Priya (Jaypee Brothers Medical Publishers, 2014)
Cataracts are a very common condition whereby the lens of the eye becomes cloudy causing blurred vision. Over time, a cataract can get worse, eventually leading to blindness if untreated. Cataracts are the most common cause of blindness worldwide. Phacoemulsification surgery is the most widely used method for cataract management. This book presents ophthalmic surgeons and trainees with the latest techniques in the management of complications in cataract surgery. Each technique is illustrated with high quality clinical photographs, a detailed description covering the whole procedure, from basic principles to minute surgical details, and extensive references. Two DVD ROMs demonstrate the various techniques. Key points Presents latest techniques in management of complications in phaco surgery Highly illustrated with clinical photographs Includes two DVD ROMs demonstrating surgical techniques Extensive references for further reading